The dissorophoid temnospondyl Parioxys ferricolus from the early Permian (Cisuralian) of Texas. (July 2022) - Schoch, Rainer R.; Sues, Hans-Dieter
Abstract: Parioxys ferricolus Cope, 1878 is a long-neglected taxon of dissorophid temnospondyls from the early Permian (Cisuralian) of Texas. Reexamination of the original material and preparation of a previously undescribed specimen shed some light on the ontogeny and reveal numerous eucacopine features. P. ferricolus is characterized by: (1) a preorbital region 1.5 times as long as the posterior skull table in juveniles and twice as long in adults, (2) a parietal only two-thirds the length of the frontal, (3) interpterygoid vacuities shorter than half the skull length, (4) choanae posteriorly extended, and (5) vomer with enlarged, V-shaped median depression. P. ferricolus is found nested with Kamacops acervalis Gubin, 1980, with which it shares synapomorphies in the palate, within the dissorophid clade Eucacopinae.